Kemampuan Komunikasi Matematis pada Materi Volume Bangun Ruang Siswa Kelas V Sekolah Dasar - Anisa Dwi Rahayu; Ryky Mandar Sary; Bagus Ardi Saputro (IAIN Kediri, 2021)
This study aims to analyze the mathematical communication skills of students on the volume of blocks and cylinders in class V SDN Grogol 01 Demak. The approach used in this research is a qualitative approach with a descriptive method. The research instrument uses tests, interviews and documentation. The results obtained are the mathematical communication skills of students in the volume of geometric material which are in the very good category of 0% or as many as 0 students, the good category is 13.33% or as manyas 2 students and the sufficient category is 86.67% or as many as 13 students. . In general, the value of students' mathematical communication skills on the volume of blocks and cylinders is quite good on average